ROCK MASS CLASSIFICATION FOR SEDIMENTARY ROCK MASSES IN INDONESIA COAL MINING AREAS - Saptono, Singgih; Yulianto, M. Rahman; Vergiagara, Vega; Sofyan, Herry (Universitas Pembangunan Nasional Veteran Yogayakarta, 2020)
The stability of rock slopes is important for the safety of personnel and equipment in the open pit mine. Slope instability and failure occur due to many factors such as adverse slope geometry, geological discontinuities, weak or weathered slope material due to weather influences. External loads such as high rainfall and seismicity could play an important role in slope failure. For this reason, a precise classification of rock mass is needed for the basis of determining technical policy. Rock slopes in open pit coal mining areas, especially in Indonesia, are characterized by applying various rock mass classification systems, such as Rock Mass Rating (RMR) and Geological Strength Index (GSI), because the study area comprises well exposed rock formations. In the RMR system, there are five main parameters viz. Uniaxial Compressive Strength (UCS) of rocks, Rock Quality Designation (RQD), spacing of discontinuity, discontinuity conditions, and groundwater conditions were considered. In this paper, several rock mass classification systems developed for the assessment of rock slope stability were evaluated with the condition of rock slopes in the tropics, especially Indonesian region, particularly in sedimentary rocks in the open pit coal mining area in order to get the corrected GSI equation used to characterize rock slopes based on quantitative analysis of rock mass structure and surface conditions of discontinuities.